Whole-Process Treatment of Combined Small Cell Lung Cancer Initially Diagnosed as “Lung Squamous Cell Carcinoma”: A Case Report and Review of the Literature - Dong, Yong; Li, Qijun; Li, Da; Fang, Yong; Wang, Chongwei (Frontiers in Immunology, 2022)
The rarity and complexity of histology lead to the low diagnosis rate and high misdiagnosis rate of combined small cell lung cancer (C-SCLC). Nowadays, C-SCLC has no commonly recommended therapeutic regimen, mainly conforming to SCLC treatment. Here, we report a patient initially diagnosed as IIIA "lung squamous cell carcinoma" by a small specimen. Radical resection was achieved after neoadjuvant immunochemotherapy, and the final surgical pathology was C-SCLC containing three different histological components. Moreover, in the literature review, we explored the therapeutic effect of neoadjuvant immunotherapy in C-SCLC, expounded the therapeutic conflicts among heterogeneous components, and analyzed the pathology complexity at the tissue, cell, and molecule levels in-depth, including possible genetic characteristics, origin, and evolution by next-generation sequencing (NGS).